Аbout using games in language teaching (Journal of actual problems of jurisprudence, 2019)
Nowadays games are considered the most important and effective methods of teaching a language. Particularly,their communicative approach and tremendous stimulating role are emphasized. While using games in classesthe teacher should also take into account factors such as language level of the students and topic of the lesson.The article also gives the examples of games which can be used at a language lesson.